In vitro antibacterial effect of deconex and sodium hypochlorite against bacterial taxa isolated from dental units - Amin, Mansour (Infect Drug Resist, 2019)
Purpose: Dental unit’s environment and relevant instruments are a major source of infectious diseases caused by a variety of microorganisms. The application of various disinfectants is one of the most effective methods for reducing or eliminating microbial contamination. The objective of this study was to evaluate the antibacterial effects of deconex and sodium hypochlorite against bacterial taxa isolated from dental unit’s environment of Ahvaz Jundishapur University of Medical Sciences, southwest of Iran. Methods: In order to evaluate the quality of disinfection, sampling was performed from different parts of 100 clinical units. For bacterial recovery and isolation, samples were enriched and cultured onto different microbiological culture media. Species identification was carried out using phenotypic and molecular methods (16S rDNA sequence analysis). In vitro activity of sodium hypochlorite and deconex were determined by the broth micro-dilution method. Results: According to conventional techniques, Bacillus spp (48%) was the most frequently encountered isolates, followed by staphylococcus spp (26%). By using both techniques, Bacillus subtilis was the most frequently encountered species (n=23, 21%), followed by Bacillus licheniformis (n=8, 7.4%), Streptococcus pneumonia (n=8, 7.4%), Staphylococcus epidermidis (n=8, 7.4%), Staphylococcus saprophyticus (n=8, 7.4%) and Staphylococcus warneri. The highest levels of contamination were observed in oral medications. The deconex had lower minimum inhibitory concentration (MIC) concentration in comparasion to sodium hypochlorite, which showed that deconex was a much more potent disinfectant. Conclusion: In conclusion, the results of the present in vitro study showed that deconex had promising results for decontamination of the tested microorganism, and it is recommended for disinfecting of dental units and environment. In this study, the high percentage of dental unit’s contamination showed the need to improve disinfection procedures, sterilization systems, and the use of an appropriate concentration of deconex and sodium hypochlorite for dental units decontamination .